Faktor-Faktor yang Mempengaruhi Net Death Rate (NDR) Stroke di RSUD Dr. Kanujoso Djatiwibowo Balikpapan Tahun 2014 - Rahmawati, Rosjidah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
This study is seeking the impact of structure and process as the quality aspect according to Donabedian's theory that affecting to the Net Death Rate (NDR) Stroke disease. Selected data source are Stroke patients, consisting of Intracerebral Haemorrhage and Cerebral Infarction at Dr Kanujoso Djatiwibowo Balikpapan Hospital in the year 2014. This study is a qualitative research using descriptive analytic retrospective method. Structure and Process Factors that are influencing each other. It reveals that Structure Factors in hospitalization that are affecting sequentially are the condition of the patient, facilities, policies and human resource. On the other hand it reveals that Process Factors include obstacle on running the primary instruction and also Hospital Accociated Infections/ HAIs occurs due to the nursing process. In Emergency Unit there is obstacle in Process Factor as the CT scan service is not available sometime. It is recommend to improve the quality of Stroke patient to overcome the Structure and Process Factors and to develop the on stop service Stroke Unit.